Architecture and neuroscience; what can the EEG recording of brain activity reveal about a walk through everyday spaces?. (18th December 2017) - Karandinou, Anastasia; Turner, Louise
Abstract: New digital media and quantitative data have been increasingly used in an attempt to map, understand and analyse spaces. Each different medium with which we analyse and map spaces offers a different insight, and can potentially increase our tools and methods for mapping spaces and understanding human experience. The emergence of such technologies has the potential to influence the way in which we map, analyse and perceive spaces. Given this context, the project presented in this paper examines how neurophysiological data, recorded with the use of portable electroencephalography (EEG) devices, can help us understand how the brain responds to physical environments in different individuals. In this study we look into how a number of participants navigate in an urban environment; between specific identified buildings in the city. The brain activity of the participants is recorded with a portable EEG device, while simultaneously video recording the route. Through this experiment we aim to observe and analyse the relationship between the physical environment and the participant's type of brain activity. We attempt to correlate how key moments of their journey, such as moments of decision-making, relate to recordings of specific brain waves. We map and analyse certain common patterns observed. We look into how the variation of the physical attributes of the built environment around them is related to the fluctuation of specific brain waves. This paper presents a specific project of an ongoing cross-disciplinary study between architecture and neuroscience, and the key findings of a specific experiment in an urban environment. Abstract : Mapping of the intensity of cognitive function associated with the Beta band of brain activity in an urban context.